Avens Root (Geum Urbanum L.) Extract Discovered by Target-Based Screening Exhibits Antidiabetic Activity in the Hen’s Egg Test Model and Drosophila melanogaster - Günther, Ilka; Rimbach, Gerald; Nevermann, Sandra; Neuhauser, Cathrina; Stadlbauer, Verena; Schwarzinger, Bettina; Schwarzinger, Clemens; Ipharraguerre, Ignacio R.; Weghuber, Julian; Lüersen, Kai (Frontiers in Pharmacology, 2021)
Medicinal plant extracts are becoming increasingly important as an alternative for traditional drugs against diabetes mellitus (DM). For this reason, we initialized a target-based screening of 111 root extracts from an open access plant extract library (PECKISH) by ascertaining their in-vitro inhibitory efficacy on α-glucosidase. The two most active extracts Geum urbanum L. (roseroot) and Rhodiola rosea L. (avens root) were further tested for their antidiabetic activities in terms of their impact on different regulatory key points of glucose homeostasis. To this end, various enzyme- and cell culture-based in-vitro assays were employed including the determination of sodium-dependent glucose transporter 1 (SGLT1) activity in Caco-2 monolayers by Ussing chambers and of glucose transporter 4 (GLUT4) translocation in a GFP-reporter cell line. Subsequently, the antidiabetic potential of the root extracts were further evaluated in in-vivo models, namely hen’s eggs test and the fruit fly Drosophila melanogaster. Avens root extract was found to be a more potent inhibitor of the enzymes α-glucosidase and dipeptidyl peptidase-4 (DPP4) than roseroot extract. Most importantly, only avens root extract exhibited antidiabetic activity in the two in-vivo models eliciting a reduced blood glucose level in the in-ovo model and a decline of the triglyceride level in a dietary starch-induced D. melanogaster obesity model. Analyses of the polyphenolic composition of the avens root extract by HPLC revealed a high content of ellagic acid and its derivatives as well as ellagitannins such as pedunculagin, stenophyllanin, stachyurin, casuarinin and gemin A. In conclusion, avens root extract represents a promising medicinal plant that should be considered in further in-vivo studies on hyperglycemia in laboratory rodents and humans.